Diseño de mejora del mecanismo de triturado en la maquina destructora de moneda de la fábrica de moneda del Banco de República - Alonso Sánchez, Edgar (Universidad Antonio Nariño, 2023)
The purpose of this proposal is to improve the mechanism of the Mint's shredding machine system, whose important function is to process coins that leave public circulation due to deterioration and coins from the manufacturing process that for different reasons do not comply with quality standards and must be destroyed following the regulations set forth by law regarding the disposal of metals with coin value, and that must be returned to the production chain as strapping for the manufacture of new coin blanks.